Information Asymmetry and Greenwashing: The Moderating Role of Corporate Social Responsibility - Dian Urna Fasihat; Lilis Marlina (Jurnal Proaksi, 2025)
Main Purpose: This study examines how information asymmetry influences greenwashing practices in Indonesian public companies and tests the moderating role of Corporate Social Responsibility performance in this relationship.Method:  The research analyzes unbalanced panel data from 95 companies listed on the Indonesia Stock Exchange for the period 2019–2023, comprising 411 observations, as ESG and CSR data for 2024 were not yet available at the time of data collection. A fixed effects regression technique is employed to test the relationships among information asymmetry, CSR, and greenwashing.Main Findings:  The results show that information asymmetry has no significant effect on greenwashing, while CSR significantly moderates this relationship. Firms with higher CSR performance exhibit lower greenwashing levels under conditions of information asymmetry.Theory and Practical Implications: Regulators need to strengthen CSR frameworks as effective mechanisms for preventing greenwashing, while investors can use CSR performance as an indicator of genuine environmental commitment. Corporate managers should view CSR investments not merely as obligations, but as protective shields for corporate legitimacy that reduce long-term reputational risks.Novelty: This study introduces a novel contribution by empirically demonstrating that CSR quality moderates the relationship between information asymmetry and greenwashing, a boundary condition that previous studies have not tested, particularly within emerging market environments.